Correlation Between Blood Lactate and Salivary Biomarkers During Exercise in Women with Hypothyroidism Treated With L-Thyroxine - Silva, Romeu Paulo Martins; Gonçalves, Alexandre; Silva, Carolina Freitas da; Bortolini, Miguel Júnior Sordi; Resende, Elmiro Santos; Gonçalves, Luis Carlos Oliveira; Magalhães-Neto, Aníbal Monteiro de; Espindola, Foued Salmen (CV Rezki Media, 2024)
Background: Hypothyroidism reduces circulating levels of thyroid hormones metabolic enzymatic activities, and the skeletal muscle's work capacity and lactatemia increase during exertion. Objectives: To analyze salivary biomarkers and blood lactate obtained in exercise stages through exhaustion and investigate their correlation. Methods: Eight females attended the University Clinical Hospital who showed a condition of subclinical hypothyroidism. Before they began replacing with L-thyroxine, they were submitted to an ergometric test to check their tolerance to effort. Eight weeks after treatment, all volunteers were again submitted to lab and ergometric tests. Saliva and blood were collected to determine total protein, nitric oxide, IgA, lactate, and lipid profile. Results: The present study identified a correlation (0.8), so the behavior of the blood lactate could explain the behavior of the salivary of total proteins by 74.22% (R2 = 0.7422). Lactate production was minimized when women underwent L-thyroxine treatment in the first six stages of exercise. Still, total salivary proteins increased for pharmacotherapy between stages 1 and 8. While salivary nitric oxide had a percentage variation between pre- and post-exercise times of 96% before the start of treatment when the same exercise was performed after eight weeks of treatment with L-Thyroxine, this variation was 150%. Conclusion: The measurement of STP is an essential marker of stress, and it is highly correlated with the most used blood marker, lactate. Regarding treatment with L-Thyroxine in women with subclinical hypothyroidism, after eight weeks of this therapy, it was possible to observe a reduction in blood lactate production after the incremental load test on a cycle ergometer, accompanied by a reduction in the concentration of SA. SNO and SIgA tended to increase in women undergoing treatment, and this treatment should be considered in subsequent studies as causing a different effect on these markers.